Noninvasive Ventilation Practice Patterns for Acute Respiratory Failure in Canadian Tertiary Care Centres: A Descriptive Analysis - Geneviève C Digby; Sean P Keenan; Christopher M Parker; Tasnim Sinuff; Karen E Burns; Sangeeta Mehta; Juan J Ronco; Demetrios J Kutsogiannis; Louise Rose; Najib T Ayas; Luc R Berthiaume; Christine L D’Arsigny; et al. (Canadian Respiratory Journal)
BACKGROUND: The extent of noninvasive ventilation (NIV) use for patients with acute respiratory failure in Canadian hospitals, indications for use and associated outcomes are unknown.